Analysis of Students' Learning Difficulties in Physical Chemistry: Perspective on Various Sub-Variable - Munawwarah Munawwarah; Sumiati Side (Jurnal Akademika Kimia, 2022)
This study aims to identify student learning difficulties in physical chemistry lectures. The subjects are 61 students in the chemistry education study program from two different classes. The research method used is mixed. Data were obtained by using instruments in the form of structured and unstructured questionnaires. Based on the results of the data analysis, several student learning difficulties were identified. Based on unstructured questionnaires, students' learning difficulties in physical chemistry material based on internal factors are caused because students find it difficult to do calculation problems, formulate derivation, and use many formulas. Based on external factors, namely the learning method used. Students prefer learning that is carried out face-to-face in a class by doing a lot of practice questions connected with applying formulas to questions and in everyday life. 55.7% of students in the medium category in learning disorder, 72% of students in the high category in learning disability, 65.5% of students in the medium category in learning dysfunction, 57% of students in the medium category in slowly learner, and 54% of students in the medium category in lower achiever. According to many students, physical chemistry is difficult. In addition, some of the causes of physical chemistry being considered difficult are confusion in analyzing questions, and learning conducted online during the Covid-19 pandemic is considered less effective. Students expect the learning method used to provide many examples and practice questions.